Responsibility for campaign grant funds in the 2024 presidential election: Hifdzul Mal's perspective - Manik, Indra Prawira; Zulham, Zulham (Trigin Publisher, 2024)
President Joko Widodo has made a decision regarding the voting day for the General Election of 2024. The substantial campaign fund required for the presidential election necessitates donors for campaign financing. However, issues arise in the implementation concerning the unclear origin of campaign grant funds.